“How to Release or Not Release, That Is the Question.” A Review of Interleukin‐1 Cellular Release Mechanisms in Vascular Inflammation - Evan Kidder; Siddhartha Gangopadhyay; Sheila Francis; Mabruka Alfaidi (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Cardiovascular disease remains the leading cause of death worldwide, characterized by atherosclerotic activity within large and medium‐sized arteries. Inflammation has been shown to be a primary driver of atherosclerotic plaque formation, with interleukin‐1 (IL‐1) having a principal role. This review focuses on the current state of knowledge of molecular mechanisms of IL‐1 release from cells in atherosclerotic plaques. A more in‐depth understanding of the process of IL‐1's release into the vascular environment is necessary for the treatment of inflammatory disease processes, as the current selection of medicines being used primarily target IL‐1 after it has been released. IL‐1 is secreted by several heterogenous mechanisms, some of which are cell type–specific and could provide further specialized targets for therapeutic intervention. A major unmet challenge is to understand the mechanism before and leading to IL‐1 release, especially by cells in atherosclerotic plaques, including endothelial cells, vascular smooth muscle cells, and macrophages. Data so far indicate a heterogeneity of IL‐1 release mechanisms that vary according to cell type and are stimulus‐dependent. Unraveling this complexity may reveal new targets to block excess vascular inflammation.